Potato consumption factors in developing countries: Case of Turkey - Metin Göksel Akpınar; Mevlüt Gül; Yavuz Taşcıoğlu; Bahri Karlı; Bektaş Kadakoğlu; Bekir Sıtkı Şirikçi; Musa Acar; Hilal Yılmaz (Cogent Food & Agriculture)
Potato has been determined as the food of future on global extent. Within this study factors affecting potato consumption were evaluated in the scope of domestic market. The main reasons behind the choice of potato consumption were its reference as future’s product as well as today’s, and the possibility to consume potato both as fresh and processed forms. In order to underline the detailed reasons, 3.072 consumers were surveyed between August and September 2020. Due to the findings, factors affecting potato consumption in the domestic market were detected as consumer awareness, consumer value and consumer convenience. These factors reflect the health awareness developed among the society within the pandemic process. This finding put forward that there is a need for public promotion of potato with reference to its food content and positive health impact. On the other hand, due to partial and complete shut-down implementations processed potato consumption has reduced and home-made fresh potato consumption has risen. This has been acknowledged as a social progress with respect to direction to healthy consumption. A declination in potato consumption was detected among two-thirds of the households due to rising prices. These findings indicated factors that affect purchases or consumption of a specific product or services under normal and extraordinary conditions need to be known. This is important for sustainability of social health and quantitative and qualitative estimation and management of both national and international market demand.